In vivo imaging of schistosomes to assess disease burden using positron emission tomography (PET). - Nicolas Salem; Jason D Balkman; Jing Wang; David L Wilson; Zhenghong Lee; Christopher L King; James P Basilion (Public Library of Science (PLoS), 2010)
Schistosomes are chronic intravascular helminth parasites of humans causing a heavy burden of disease worldwide. Diagnosis of schistosomiasis currently requires the detection of schistosome eggs in the feces and urine of infected individuals. This method unreliably measures disease burden due to poor sensitivity and wide variances in egg shedding. In vivo imaging of schistosome parasites could potentially better assess disease burden, improve management of schistosomiasis, facilitate vaccine development, and enhance study of the parasite's biology. Schistosoma mansoni (S. mansoni) have a high metabolic demand for glucose. In this work we investigated whether the parasite burden in mice could be assessed by positron emission tomography (PET) imaging with 2-deoxy-2[(18)F]fluoro-D-glucose (FDG).Live adult S. mansoni worms FDG uptake in vitro increased with the number of worms. Athymic nude mice infected with S. mansoni 5-6 weeks earlier were used in the imaging studies. Fluorescence molecular tomography (FMT) imaging with Prosense 680 was first performed. Accumulation of the imaging probe in the lower abdomen correlated with the number of worms in mice with low infection burden. The total FDG uptake in the common portal vein and/or regions of elevated FDG uptake in the liver linearly correlated to the number of worms recovered from infected animals (R(2) =0.58, P<0.001, n = 40). FDG uptake showed a stronger correlation with the worm burden in mice with more than 50 worms (R(2) = 0.85, P<0.001, n = 17). Cryomicrotome imaging confirmed that most of the worms in a mouse with a high infection burden were in the portal vein, but not in a mouse with a low infection burden. FDG uptake in recovered worms measured by well counting closely correlated with worm number (R(2) = 0.85, P<0.001, n = 21). Infected mice showed a 32% average decrease in total FDG uptake after three days of praziquantel treatment (P = 0.12). The total FDG uptake in untreated mice increased on average by 36% over the same period (P = 0.052).FDG PET may be useful to non-invasively quantify the worm burden in schistosomiasis-infected animals. Future investigations aiming at minimizing non-specific FDG uptake and to improve the recovery of signal from worms located in the lower abdomen will include the development of more specific radiotracers.